O uso de aplicativos de promoção de saúde por adolescentes do município de Rio Claro - SP - Rodrigues, Danilo Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Introdução: Nos últimos anos verifica-se um aumento do uso de smartphones e aplicativos em busca de entretenimento e lazer entre os adolescentes. No Brasil, 65% dos jovens utilizam smartphones, e sabe-se que tal uso pode contribuir para a mudança de hábito, sobretudo no aumento do tempo despendido em comportamento sedentário. Dessa forma aplicativos relacionados a saúde vem sendo criados com o objetivo de auxiliar na promoção de hábitos saudáveis. Objetivo: Levantar os principais aplicativos de smartphones relacionados à saúde utilizados por adolescentes de escolas públicas do município de Rio Claro-SP. Metodologia: Foram recrutados estudantes do ensino fundamental II e médio de 3 escolas públicas e 2 particulares do município de Rio Claro - SP, que possuíam acesso a um smartphones. Aplicou-se Anamnese Clínica, juntamente com a pergunta: “Você utiliza algum aplicativo de exercício físico ou alimentação saudável?”, o questionário socioeconômico e um questionário levantamento de aplicativos criado pelo autor. Para análise de dados foi realizado uma descritiva (média, desvio padrão e porcentagem) e verificou-se havia diferença entre os grupos meninos e meninas e adolescentes mais novos e mais velhos por meio do teste T de student (p≤0,05). Resultados: Participaram do estudo 482 adolescentes com 14,43±2,08 anos de idade, sendo que 41,5% pertence à classe econômica B2. Apenas 23 estudantes relataram que utilizam ou já utilizaram aplicativos voltados para a saúde e não houve diferença significativa entre os grupos de meninos e meninas e adolescentes mais velhos e mais novos. Conclusão: Conclui-se que os adolescentes rioclarenses utilizam poucos aplicativos de smartphones voltados para a saúde e os que utilizam são voltados para a atividade física.

Introduction: In recent years there has been an increase in the use of smartphones and apps in search of entertainment and leisure among teenagers. In Brazil, 65% of young people use smartphones, and it is known that such use can contribute to change of habit, especially in the increase of time spent on sedentary behavior. Thus, applications related to health have been created with the objective of helping the promotion of healthy habits. Objective: To survey the main smartphones applications related to health used by teenagers from public schools in the city of Rio Claro-SP. Methodology: We recruited elementary and high school students from 3 public schools in the city of Rio Claro - SP, who had access to a smartphone. We applied the questionnaires of Habitual Physical Activity of Adolescents and Clinical Anamnesis, with the question: "Do you use any application for physical activity or healthy eating?". The adolescents were separated into 2 groups according to the Level of Physical Activity (NAF), being group 1 (<150 min/week) and group 2 (≥150 min/week). For data analysis a descriptive (mean, standard deviation and percentage) was performed and the difference between the groups was tested by the student's T test (p≤0,05). Results: 354 adolescents participated in the study, with 14.7±2.0 years of age and BMI 20.7±4.2 kg/m². Group 1 (n= 206) presented mean NAF of 27.6±41.0 min/week and group 2 (n=148) mean NAF of 487.1±385.8 min/week. When verifying the use of health applications, there was a significant difference (p=0.006) between the groups. In group 2, 11.5% of students used health app’s, and in comparison, 3.9% of students from group 1 reported using some application. Results: 354 adolescents participated in the study, with 14.43±2.8 years of age,being that 41,5 % belongs to economical class B2. Only 23 students reported what use or they already used applications programs turned to the health and there was no significant difference between the groups of boys and girls and the oldest and newer adolescents. Conclusion: It is concluded that adolescents from Rio Claro use few smartphone apps focused on health, and the ones that they use, are focused on physical activity, and no difference between age group was verified.
The use of health promotion applications by adolescents in the city of Rio Claro - SP
Keywords: Educação física; Promoção de saúde; Adolescentes; Aplicativos móveis; Atividade física; Aplicativos para smartphones; Saúde; Smartphone apps; Health; Teenagers